2003
DOI: 10.4049/jimmunol.171.5.2331
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of H2-O Influence on Antigen Presentation by B Cells

Abstract: HLA-DM (DM; in mouse H2-DM) promotes the exchange of MHC class II-associated peptides, resulting in the accumulation of stable MHC class II-peptide complexes. In naive (but not germinal center) B cells, a large part of DM is tightly associated with HLA-DO (DO; in mouse H2-O), but the functional consequence of this association for Ag presentation is debated. Here, we have extended previous studies by examining the presentation of multiple epitopes after Ag internalization by fluid phase endocytosis or receptor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 39 publications
4
42
0
Order By: Relevance
“…H2-O −/− B cells outcompeted WT B cells by ∼2-to 5-fold, but did not completely take over the GC niche. This suggests that H2-O-dependent modulation of Ag presentation may be subtle, which is supported by previous studies that examined presentation on the cellular level and found varying effects of H2-O depending on the specific epitope examined (9,(11)(12)(13)(14)(15)25). Nevertheless, small differences in Ag presentation, especially when considering a complex Ag mix containing many individual epitopes, could have a considerable impact on the immune response.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…H2-O −/− B cells outcompeted WT B cells by ∼2-to 5-fold, but did not completely take over the GC niche. This suggests that H2-O-dependent modulation of Ag presentation may be subtle, which is supported by previous studies that examined presentation on the cellular level and found varying effects of H2-O depending on the specific epitope examined (9,(11)(12)(13)(14)(15)25). Nevertheless, small differences in Ag presentation, especially when considering a complex Ag mix containing many individual epitopes, could have a considerable impact on the immune response.…”
Section: Discussionsupporting
confidence: 55%
“…Studies using MHCII-peptide-specific Abs, TCR Tg T cells, or T-cell hybridomas have shown that H2-O variably and unpredictably affects the presentation of individual peptides (9,14,15). Therefore, rather than further study T-cell responses to the presentation of individual peptides, we measured the ability of GC B cells to obtain T-cell help from the pool of endogenous polyclonal CD4 + T cells.…”
Section: Np-specific H2-o −/− B Cells Preferentially Populate the Gc mentioning
confidence: 99%
“…2a, right panel). As previous studies have reported a requirement for the MHC-like molecule H-2DM in BCR-mediated antigen presentation, 46 we also performed antigen presentation assays using the A20 mutant 3A5, which lacks functional H-2DM. synthetic p84-104 peptide by A20-3A5 B cells was similar to that of A20 cells (Fig.…”
Section: Generation Of Aggrecan-specific B Cellsmentioning
confidence: 99%
“…Hence, upon productive Ag presentation with the hybridoma's cognate I-A b -restricted Ag, the hybridoma would express eGFP. BMMfs from WT and Cybb 2/2 mice were exposed to 1 mg/ml HEL for 6 h and individual hybridomas were added and incubated with the BMMfs for 16 h. Presentation efficiency of each HEL epitope was determined by measuring eGFP expression by flow cytometry and is presented relative to GFP expression induced by nonspecific hybridoma activation by 50 ng/ml PMA and 1 mg/ml ionomycin (25,26).…”
Section: Assessment Of Pattern Of Intraphagosomal Proteolysismentioning
confidence: 99%
“…In vitro assessment of Ag processing and presentation (25,26) were stably transfected with a pcDNA3 construct that contained enhanced GFP (eGFP) under the control of a NFATenhanced IL-2 promoter (pNFATeGFP) as previously described (25)(26)(27)(28). Hence, upon productive Ag presentation with the hybridoma's cognate I-A b -restricted Ag, the hybridoma would express eGFP.…”
Section: Assessment Of Pattern Of Intraphagosomal Proteolysismentioning
confidence: 99%